A Multi-Criteria Decision Framework for network selection over LTE and WLAN. (November 2017) - Drissi, Maroua; Oumsis, Mohammed; Aboutajdine, Driss
Abstract: The most appealing topic for next generation wireless networks – 5G and upcoming generations – is the vertical handover, as many heterogeneous wireless communication technologies have been introduced recently to fulfil the needs of mobile users under all circumstances. Especially with the growing applications that are greedy in terms of Quality of Service (QoS). Thus, being Always Best Connected (ABC) remains a difficult task to achieve. The purpose of this article is to tackle the network selection issue levering a combination of Multi-Criteria Decision Making (MCDM) methods to ensure that appropriate network is selected for a certain type of traffic and considering a number of QoS metrics that due to their interdependency, a weight distribution phase is required. To ascertain thoroughly the weights of QoS metrics impacting the decision for each application, Analytical Hierarchy Process (AHP) is generally applied. But its classical form comes with biased rules that are dealt with through an enhanced version FAHP (Fuzzy AHP) that has proven its performance when combined with other well reputed ranking methods, namely: "Multiplicative Exponential Weighting (MEW)", "Simple Additive Weighting (SAW)", "Technique for Order Preference by Similarity to an Ideal Solution (TOPSIS)" and "VlseKriterijumska Optimizacija I Kompromisno Resenje (VIKOR)". The implementation and simulation experiments in LTE and WLAN environments using Network Simulator NS3 are presented in order to evaluate the reviewed algorithms focusing on Packet Delay and Packet Loss Rate as key selection criteria. The empirical results show that FAHP algorithms over perform the classical AHP ones. The most suitable algorithms combination will be assessed and suggested for each type of traffic.